Simulation study on the physicochemical properties of Fe3O4 nanoparticles as drug delivery vehicles for dopamine replacement therapy of Parkinson's disease. (June 2022) - Harris, R.A.
Abstract: A simulation study to investigate the physicochemical properties of Fe3 O4 nanoparticles as a drug delivery vehicle for dopamine replacement therapy is done. Albumin is added as an additional permeation enabling molecule to successfully cross the blood-brain-barrier. Both PEGylated and non-PEGylated systems are investigated to report on the post-synthesis stability of these systems and discover pathways for NP hydrodynamic size tunability without compromising the NP stability. This is done for nanoparticle sizes varying from 1.0 to 7.0 nm and within a molecular dynamics study with a Monte Carlo simulated annealing scheme. Bonding modes are investigated with reference to chemisorption and physisorption in the context of bond strength (binding energy) as a function of the molecule (drug) loading on different sized nanoparticles. Graphical Abstract: ga1